Dating the Côa Valley rock art 25 years later: an archaeological and geoarchaeological approach - Santos, André Tomás (2021)
The dating of rock art is one of the main inherent problems of the research of this type of archaeological evidence. This task is not, however, devoid of difficulties, stylistic comparison being the only available method to accomplished it in countless occasions. In the Côa Valley, we do not discard stylistic comparison, such a method being used as an essential complement of a wider strategy that we will describe in this text. This strategy involves the use of multivariante statistics and archaeological and geoarchaeological evidence that was obtained during the research carried out in the region. The paper closes with the characterization of each of the graphic phase identified in the Côa Valley by the application of our strategy and with a demonstration, with several examples, of the importance of rock art chronocultural attribution in other problematics of the research.